Hemodynamic of the patent ductus arteriosus in neonates with modified Blalock-Taussig shunts. (April 2020) - Zhang, Neichuan; Yuan, Haiyun; Chen, Xiangyu; Liu, Jiawei; Zhou, Chengbin; Huang, Meiping; Jian, Qifei; Zhuang, Jian
Highlights: The hemodynamic effect of nonclosure of Patent ductus arteriosus (PDA) on modified Blalock-Taussig shunt (MBTS) was investigated numerically. MBTS with nonclosure of PDA plays an active role in preventing early acute shunt failure and produced a better hemodynamic environment including lower blood velocity, energy loss, WSS values at MBT shunt, smaller vortex regions, higher oxygen content (Sao2) and more uniform velocity distribution in the LPA and RPA compared to MBTS with closure of PDA. However, excessive PA flow induced by nonclosure of PDA may result in a series of complication. MBTS with nonclosure of PDA could be preferred for cases with very low PA overflow risk and maybe benefit for patients with underdeveloped myocardium due to lower energy dissipation. MBTS with closure of PDA could be preferred for cases with very high PA overflow risk. Abstract: Background and objective: Studying the hemodynamic effects of nonclosure of patent ductus arteriosus (PDA) on the modified Blalock-Taussig shunt (MBTS) is beneficial for surgical PDA management. In the present study, the effect of PDA on MBTS was investigated numerically. A series of parameters including energy loss, wall shear stress (WSS), and left/right Pulmonary artery (LPA/RPA) flow ratio were computed from simulations to analyze the hemodynamic effects of PDA on MBTS. Methods: To ensure the universality of the research conclusions, three typical models, including models with a well-developed RPA, a symmetrically-developed pulmonary artery(PA) and a well-developed LPA, were constructed based on patient-specific pre-surgery clinical data sets. A commercial CFD solver ANSYS-Fluent software was adopted for this study. A pressure-based solver for incompressible Newtonian flows, the K-omega based shear-stress-transport model and a second-order accurate numerical discretization scheme were employed for simulation. Results: Our results show that MBTS with nonclosure of PDA is accompanied by lower blood velocity, energy loss and WSS values at the MBT shunt; smaller vortex regions; higher oxygen content(Sao2 ) and PA flow; and more uniform velocity distribution in the LPA and RPA than MBTS with closure of PDA. If the PDA was not closed when performing primary MBTS, a series of hemodynamic changes occurs during PDA closure in postoperative recovery: the energy loss, PA flow and Sao2 decrease, while the oxygen delivery(Do2) and WSS values at the MBT shunt increase. Conclusion: Nonclosure of PDA could provide a better hemodynamic environment and play an active role in preventing early acute shunt failure. It could be preferred for cases with very low PA overflow risk and may benefit patients with an underdeveloped myocardium due to its lower energy dissipation than PDA closure. However, excessive PA flow induced by nonclosure of PDA may result in a series of complications. Surgeon's decision-making process with respect to PDA management should consider the individual patient to achieve optimal postoperative recovery.